Návrh řešení dvojí kvality potravin pomocí technologie Blockchain - Kopec, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Diplomová práca sa zaoberá návrhom nasadenia a princípu fungovania systému za- loenom na technológií blockchain, ktor by iastone eliminoval problém dvojitej kvality potravín v EÚ. Teoretická as je zameraná na vysvetlenie princípov techno- lógie blockchain, anal zu problému, EÚ trhu a súasn ch rieöení. Praktická as sa venuje samotnému návrhu systému.

The goal of this diploma thesis is to propose a system based on blockchain technology that is dealing with dual food quality problem in countries of the EU. The theore- tical part of the thesis explains basic principles of blockchain technology, provides an analysis of the dual food quality problem, EU market and the current blockchain implementations in food industry. The practical part focuses on the solution design of such a system itself.
Solution design of dual food quality problem through Blockchain technology
Keywords: blockchain; potraviny; produkty; kvalita; transparentnos; Európska Únia; blockchain; goods; products; quality; transparency; European Union